Population fluctuation of Melanagromyza sojae (Diptera: Agromyzidae) on chickpea and soybean crops and update of its geographical distribution in Argentina - Augusto S. Casmuz; Martin A. Vera; Lourdes L. Suarez; Jerson C. Guedes; Gerardo Gastaminza; Maria G. Murua (Journal of Plant Protection Research)
Melanagromyza sojae, the soybean stem fly (Zehntner) (Diptera: Agromyzidae), is a new pest in soybean and chickpea crops in South America. The objective of this study was to determine population fluctuations of M. sojae in both crops using adults caught in yellow sticky traps and by sampling injured plants. Additionally, an update of its geographical distribution in Argentina is provided. Adults of this species were collected for multiple years and during the cycles of both soybean and chickpea crops, on volunteer soybean plants, and during periods when the crops were not present. Injuries caused by M. sojae occurred throughout the growing period of chickpea and the reproductive stages of soybean. The highest infestation level was registered in chickpea crops. Regarding the distribution of M. sojae, we have reported Medicago sativa, Vigna radiata, Mellilothus sp., Helianthus annuus, Carthamus tinctorius, Heliotropium sp., Glandularia sp., and Parthenium sp. for the first time as new host plants in Argentina. The presence of M. sojae in Chaco province (Argentina) was also reported for the first time. Finally, the highest percentage of infestation registered in chickpea crops shows that M. sojae is a pest in chickpea-growing areas in Argentina where this pest is widely distributed. It is of vital importance to develop effective control methods, to research and recommend efficient management strategies and control methods for M. sojae in chickpea.